Building expert agreement on the importance and feasibility of workplace health promotion interventions for nurses and midwives: A modified Delphi consultation. (16th July 2017) - Perry, Lin; Nicholls, Rachel; Duffield, Christine; Gallagher, Robyn
Abstract: Aim: To use a Delphi panel to determine the relative importance and feasibility of workplace health promotion interventions to promote and support the health of the Australian nursing and midwifery workforce. Background: The nursing workforce experiences rates of ill health above that of other workforces, yet there is little investment in workplace health promotion. Design: The study used a modified Delphi design conducted between September and November 2015. Methods: Eleven of 19 purposively selected expert panellists discussed, rated and provided feedback through two rounds of an electronic questionnaire about the relative importance and feasibility of 46 workplace health promotion interventions and processes for nurses and midwives. Scores for importance and feasibility were calculated and ranked and a composite score of importance multiplied by feasibility. Results: Mental health strategies were prioritized as the most important and feasible of the intervention topics, followed closely by healthy eating and physical activity interventions; smoking cessation ranked lowest. The most highly ranked interventions targeted healthy eating, stress management and resilience training. Highest ranked processes to support development of a healthy work environment included intersectoral collaboration and employee wellness groups. Conclusions: Study findings prompt consideration of health promotion opportunities to support nurses' health and well‐being. Findings identified key workplace health promotion priorities and provide direction for policy makers and managers to promote nursing and midwifery workforce health.